2021
DOI: 10.1242/jcs.258894
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 disrupts interaction of sortilin with fatty acid-binding protein 7 essential to promote lipid signaling

Abstract: Sortilin is a neuronal receptor for apolipoprotein E. Sortilin-dependent uptake of lipidated apoE promotes conversion of polyunsaturated fatty acids (PUFA) into neuromodulators that induce anti-inflammatory gene expression in the brain. This neuroprotective pathway works with apoE3 but is lost with apoE4, the main risk factor for Alzheimer's disease (AD). Here, we elucidated steps in cellular handling of lipids through sortilin, and why they are disrupted by apoE4. Combining unbiased proteome screens with anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Moreover, in AD brains of patients expressing ApoE ε4, there are reduced levels of FABP7, and this alters PUFA cerebral content and their role as anti-inflammatory molecules [ 105 ].…”
Section: Fatty Acid Binding Proteins In Neurodegenerationmentioning
confidence: 99%
“…Moreover, in AD brains of patients expressing ApoE ε4, there are reduced levels of FABP7, and this alters PUFA cerebral content and their role as anti-inflammatory molecules [ 105 ].…”
Section: Fatty Acid Binding Proteins In Neurodegenerationmentioning
confidence: 99%
“…Additionally, Sortilin/NTSR3 has been shown to interact with the receptor of Nerve Growth Factor (NGF), the p75 neurotrophin receptor (p75NTR), to trigger neuronal apoptosis induced by the precursor of Nerve Growth Factor (pro-NGF) [ 27 , 28 ] and the precursor of Brain-Derived Neurotrophic Factor (pro-BDNF) [ 29 , 30 ]. Recently, it was identified that Sortilin/NTSR3 acts as a receptor for the brain lipids carrier Apolipoprotein E (apoE), which confers the most important genetic risk factor for Alzheimer’s disease (AD), demonstrating the involvement of Sortilin/NTSR3 in the neuroprotective action of apoE in AD pathology [ 31 ]. Finally, the role of Sortilin/NTSR3 as a biomarker of risk in cardiovascular disorders in humans has been largely confirmed [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent evidence suggests that APOE and FABP7 may interact, with the APOE isoform determining the functional expression of FABP7 ( Asaro et al, 2021 ). In mouse brains expressing the ApoE ε3 isoform (the most common isoform), this transporter delivers lipids to the neuronal receptor sortilin, which mediates the transfer of lipids from the exterior of the cell to the interior ( Carlo et al, 2013 ).…”
Section: Lipid Transport In Alzheimer’s Diseasementioning
confidence: 99%
“…Sortilin directs the uptake and conversion of polyunsaturated fatty acids into endocannabinoids, lipid-based neurotransmitters that act through nuclear receptors to sustain neuroprotective gene expression in the brain ( Asaro et al, 2020 ). In a mouse model, sortilin was also shown to promote the stability of FABP7 in an APOE isoform-dependent manner, with ApoE ε3 promoting the proper intracellular sorting of FABP7 and ApoE ε4 disrupting it ( Asaro et al, 2021 ). APOE isoform-related differences in FABP7 have also been seen in humans ( Asaro et al, 2021 ).…”
Section: Lipid Transport In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation